Preventive Effect of Diabegon, a Polyherbal Preparation, During Progression of Diabetes Induced by High-Fructose Feeding in Rats - Hariom Yadav; Shalini Jain; GBKS Prasad; Mukesh Yadav (Elsevier, 2007)
In the present study, the polyherbal preparation diabegon, containing 18 plant extracts with hypoglycemic activity, was evaluated for its preventive effect during progression of type 2 diabetes in high-fructose-diet-fed rats. Oral administration of diabegon (100 mg/kg body weight) delayed development of glucose intolerance for 4 weeks in comparison with the diabetic control group, and the effect of diabegon was compared to that of the standard insulin sensitizer drug rosiglitazone. Diabegon treatment also ameliorated the elevation of glycosylated haemoglobin, liver glycogen content, plasma insulin, homeostasis model assessment, free fatty acids, triglycerides, total cholesterol, LDL-cholesterol, and VLDL-cholesterol, whereas it increased HDL-cholesterol after 56 days of treatment (P<0.05). The mechanism of action by which diabegon attenuates insulin resistance and dyslipidemia may be through induction of peroxisome proliferator-activated receptor-γ and lipoprotein lipase activity in peripheral tissues (muscles). Moreover, diabegon administration for 56 days also produced no alteration in liver and kidney function tests, which seems to indicate its non-toxicity during treatment. Our present results suggest that diabegon may be included in diabetes mellitus treatment regimens, as a drug with good antidiabetic actions but no toxic manifestations. Keywords:: diabetes, diabegon, high fructose, herbal, antidiabetic plant